A quantitative study of the emotional outcome of people caring for stroke survivors. - Dennis, M; O'Rourke, S; Lewis, S; Sharpe, M; Warlow, C (1998)
BACKGROUND AND PURPOSE: Although the physical and, to a lesser extent, emotional outcome of stroke survivors has been well documented, there are far fewer data relating to the outcomes of those who care for them. We aimed to describe the outcome of those caring for stroke patients and to identify both patient and caregiver factors that are associated with poor caregiver outcomes. METHODS: As part of a randomized trial to evaluate a stroke family care worker, we identified 417 patients (67% of all referrals to our institution). We followed up 376 survivors of whom 246 identified a caregiver at a 6-month follow-up interview. The patients and caregivers were asked to complete 2 measures of emotional distress ( 30-item General Health Questionnaire [GHQ-30] and Hospital Anxiety and Depression [HAD] Scale). A regression analysis was used to identify factors that were independently associated with poor caregiver outcomes. RESULTS: Fifty-five percent of responding caregivers scored more than 4 on the GHQ-30, indicating that emotional distress is common in this group. Caregivers were more likely to be depressed if the patients were severely dependent (P<0.01) or emotionally distressed themselves (P<0.01). Female caregivers reported more anxiety (median HAD=8) than male caregivers (median HAD=5; P<0.01) but caregivers' levels of anxiety were not so clearly related to the patients' degree of physical disability as their levels of depression. Caregivers suffered more emotional distress if the patients had been dependent before their strokes. CONCLUSIONS: These data may help to identify those caregivers at greatest risk of poor emotional outcomes and thus help in the planning of trials and delivery of interventions aimed at preventing or treating distress among caregivers.